(untitled) (Journal of Laboratory Animal Science, 2019)
Swine is the optimal model species for investigation of a large number of human diseases and have made valuable contributions to almost every field of human medicine. Similarities in the cardiovascular, urogenital, integument, skeletal and digestive systems of swine to humans have contributed to increased use of pigs in research. Swine offer additional advantages over other species by having a renal anatomy and function very similar to human. Studies have lead to the development of a highly warranted vaccine for various diseases using swine as model. In animal models, whole cell vaccination resulted in hypersensitivity reactions, so new strategies are devised. The first immunogenic molecule described was the major outer membrane protein and this molecule has been studied in great detail as a candidate vaccine. Even though complete protection was not obtained, reduced shedding was observed and vaccine trials in SPF pigs as animal models using naked DNA as a vaccine resulted in stimulation of both the humoral and the cellular immune responses indicating progress in vaccine development. This model is also used in pharmacokinetic studies, evaluating ADME, interspecies variations in CYP subfamily. Further, because of their similarities with humans, pig tissues and organs are currently being used and studied as human xenografts with the potential for increased use in this area in the near future.